Study of the inhibitory effect of a few pure molecules and natural extracts on four key enzymes of Alzheimer's disease with molecular docking and ADMET analysis - SERSEG , Talia; BENAROUS Khedidja (Université de Laghouat , Bibliothèque centrale, 2021)
The search for active compounds from plants – for the development of new potent anti-AD drugs or as an alternative strategy for treatment of Alzheimer’s disease- is the subject of many scientific and medical research. From this perspective, we aimed through this study to screen the antiacetycholinesterase effect of the crude extract of seven plants, and explored the possibility and predicted the activity of the major compounds of these extracts using in silico methods against Acetylcholinesterase (AChE), Butyrylcholinesterase (BuChE), Beta-secretase (BACE1), and Monoacylglycerol lipase (MAGL). Hence, determining the main interactions in the inhibitor enzyme complex. In the first part, we estimated the amount of phenolic compounds and flavonoids in these plants. The results showed that these plants contain a considered amount of phenolic compounds whose contents in hexane, ethyl acetate, and methanol extracts vary between 0.026±0.004 to 29.11±0.504 mgGAE/gDM. For flavonoids, the levels in the extracts vary between 0.00 to 7.690±0.481 mgQE/gDM. In the second part, we studied the inhibitory effect of Arbutus unedo L, Coriandrum sativum, Juniperus oxycedrus, Juniperus phoenicea, Lavandula stoechas, Saussurea costus and Lepidium sativum extracts on acetylcholinesterase using the Ellman method. The results confirmed the capacity of these plants to inhibit the enzyme with a value of IC50 0.358±0.005 to 2.489±0.154 mg/mL. With the exception of A.unedo L (EtOAc), L. stoechas (Meth) which has no inhibitory activity. In the third part, we achieved a molecular docking study using Autodock Vina. Furthermore, the drug-likeness and ADMET properties of the major compounds in studied plants were also evaluated. All the complexes of studied molecules with the four enzymes show significant, several, and different interactions. The major components published in the literatures- of J.oxycedrus, J.phoenicea, and L.sativum namely: Catechin, Myricetin-O-pentoside and Lepidine B respectively bind tightly to AChE and BuChE as much as galantamine and donepezil. Expect the major molecules of S.costus that exhibit a low affinity to studied enzymes. We suggest that Lepidine B is a non-competitive inhibitory by interacting with PAS of AChE and BuChE, therefore it is capable to prevent the HuAChE-induced Aâ aggregation. The results of our study indicate that the studied plants are promising resources for anti-AD drugs such as Catechin, Myricetin-O-pentoside, and Lepidine B and might use to prevent Alzheimer's disease due to their roles as potent inhibitors for AChE, BuChE, BACE1, and MAGL. Indeed, they could inhibit Aâ fibrillogenesis.